2011
DOI: 10.1111/j.1468-2370.2011.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and Safety Management in Organizations: A Review

Abstract: In examining the research literature on occupational health and safety (OHS), this paper argues that the growth in the number of specialists in OHS has resulted in an emphasis on policy and practice away from more scholastic concerns previously addressed by academics in the disciplines of psychology and sociology. A hiatus has occurred, and this is evidenced by the general absence of studies in management, even though OHS is increasingly seen as a key operational and strategic concern of business organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 112 publications
(164 reference statements)
0
81
0
Order By: Relevance
“…Research on operations management demonstrates the importance of proper management of human resources in business and accurate operation of OHS (Zanko & Dawson, 2012). In the same way, companies are increasingly being asked by different stakeholders to manage their OHS issues adequately, systematically, and transparently .…”
Section: Barriers To Occupational Health and Safety Management In Smamentioning
confidence: 99%
“…Research on operations management demonstrates the importance of proper management of human resources in business and accurate operation of OHS (Zanko & Dawson, 2012). In the same way, companies are increasingly being asked by different stakeholders to manage their OHS issues adequately, systematically, and transparently .…”
Section: Barriers To Occupational Health and Safety Management In Smamentioning
confidence: 99%
“…Michael et al (2005) suggest that employee perceptions of management's concern for employee well-being through a dedication to safety may result in positive outcomes beyond improved safety performance. Perceived management commitment to safety has been linked to employee attitudes such as: job satisfaction, organisational commitment and turnover (Michael et al, 2005;Zanko and Dawson, 2012). A meta-analysis by Faragher et al (2005) found evidence that job satisfaction was associated with workers' mental health but the evidence for a link with subjective physical health was weaker.…”
Section: Introductionmentioning
confidence: 99%
“…As it pertains to safety, the initial investigation of broader leadership studies warrants perusal through the research of Zanko and Dawson (2012). Conclusions from this research detailed that traditional occupational health and safety (OHS) has focused on policies and systems; there is a notable lack of research on OHS safety leadership behaviours.…”
Section: Safety Leadershipmentioning
confidence: 99%